Empowering International Students to Succeed: An Innovative and Beneficial Initiative for Health Professions - Penman, Joy; Malik, Gulzar; Chu, Eli; Kett, Giselle; Hampton, Kerry; Thomacos, Nikos; Ebrahimi-Zanjani, Maya; Zhong, Yaping; McKenzie, Wendy (Journal of International Students, 2021)
International students report higher sociocultural and academic stress when settling into a new university compared with their local counterparts. Three disciplines in the health professions collaborated to create a transition program addressing international student health and well-being in Australia. Commencing students and senior student mentors participated in a four-session program of activities to reflect on their current study/work practices and learn self-management strategies. They developed plans for coping with cultural, language, academic, and social barriers, and assisted in improving physical and mental health and well-being. Of the 26 participants who attended sessions, 15 participated in in-depth interviews. Facilitating adjustment, establishing relationships, gaining new skills and knowledge, and transforming beliefs and behavior were the four themes identified that captured and explicated the impact of the initiative. Although limited by the number of student participants, the program demonstrated a positive impact in creating a supportive learning environment for international students.